Counter acts: practices of ‘anti-anti racism’ in France and the USA - Garner, Steve (Frontiers in Sociology, 2024)
In various European countries, the post-fascist nationalist and populist parties identified by Ignazi in the early 1990s ‘silent counter-revolution’ now hold power, at least as part of coalitions. The values they represent can no longer be described as marginal to the national conversations on identity, immigration and security, issues that revolve around racialized understandings of the social world. In recent years we have observed similar phenomena in the Americas and Asia (with the Trump, Bolsonaro and Modi regimes). Moreover, state actors and social movements have developed initiatives aimed at undermining and reversing any small—sometimes symbolic—progress made toward equality. Various attacks on academic concepts relating to racism in the UK, France and the USA, for example, are not isolated stand-alones but elements of a global pushback against such ideas, orchestrated and encouraged by the nationalist political right, working through media, government and funded civil society organisations. These discourses redraw national identity to portray antiracist work as unpatriotic and indeed threatening to the nation. One of the strands in France’s long and fractious conversation about its colonial history and postcolonial present has constructed an opposition between republican values and Muslims. The American right’s long war on racial equality has generated a campaign to eradicate ‘critical race theory’ from education. These two examples illustrate and identify common elements and specifics in a global trend whereby the concepts used by activists and social scientists to understand and frame struggles for racial equality are deliberately and strategically invalidated and vilified in the public domain, and ideologically produced as un-patriotic. I call this discourse ‘anti-anti racism’. These efforts are part of wider campaigns, or ‘counter acts’, aimed at reversing progressive political gains from the last half century.